Pengaruh Profesionalisme Guru, Penggunaan Media Daring, Dan Keaktifan Siswa Terhadap Kepuasan Belajar Siswa Jurusan AKL SMK IPIEMS Surabaya - Nabila Nur Izza; Eko Wahjudi (Jurnal Pendidikan Akuntansi (JPAK), 2023)
Researchers carried out research in order to identify and test the variables of teacher professionalism, use of online media, and student activity on student satisfaction in the AKL major of SMK IPIEMS Surabaya, either partially or simultaneously. This type of research is quantitative. Data was collected using a questionnaire method and multiple linear regression data analysis techniques using IBM SPSS v.25. Based on the research that has been done, the results obtained are: (i) teacher professionalism with a sig. 0.980>0.05 has no effect on learning satisfaction, (ii) the use of online media with a sig value. 0.000 <0.05 has an influence on learning satisfaction, (iii) student activity with a sig. 0.134>0.05 had no effect on learning satisfaction, and (iv) teacher professionalism, use of online media, and student activity with a sig. 0.000 <0.05 and R2 of 0.177 have a simultaneous effect of 17.7% on student learning satisfaction.